Ethnic disparities in COVID-19 mortality and cardiovascular disease in England and Wales between 2020-2022 - Marta Pineda-Moncusí; Freya Allery; Hoda Abbasizanjani; David Powell; Albert Prats-Uribe; Johan H. Thygesen; Angela Wood; Christopher Tomlinson; Amitava Banerjee; Ashley Akbari; Antonella Delmestri; Laura C. Coates; et al. (Nature Communications)
Abstract An increased risk of COVID-19 mortality risk among certain ethnic groups is well-reported, however data on ethnic disparities in COVID-19-related cardiovascular disease (CVD)  are lacking. We estimated age-standardised incidence rates and adjusted hazard ratios for 28-day mortality and 30-day CVD by sex for individual ethnicity groups from England and Wales, using linked health and administrative data. We studied 6-level census-based ethnicity group classification, 10-level classification (only for Wales), and 19-level classification as well as any ethnicity sub-groups comprising >1000 individuals each (only for England). COVID-19 28-day mortality and 30-day CVD risk was increased in most non-White ethnic groups in England, and Asian population in Wales, between 23rd January 2020 and 1st April 2022. English data show mortality decreased during the Omicron variant’s dominance, whilst CVD risk [95% confidence interval] remained elevated for certain ethnic groups when compared to White populations (January-April 2022): by 120% [28-280%] in White and Asian men and 58% [32-90%] in Pakistan men, as compared to White British men; and by 75% [13-172%] in Bangladeshi women, 55% [19-102%] in Caribbean women, and 82% [31-153%] in Any Other Ethnic Group women, as compared to White British women. Ethnically diverse populations in the UK remained disproportionately affected by CVD throughout and beyond the COVID-19 pandemic.